1994
DOI: 10.1002/bit.260430816
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypic culture systems for liver and bone marrow: Evidence for the development of functional tissue in vitro and following implantation in vivo

Abstract: Stromal cell-associated liver cell and bone marrow (BM) culture on three-dimensional nylon screen or polyglycolic acid (PGA) felt templates conveys certain functional advantages to the parenchyma of these tissues. Hepatic parenchymal cells (PC) manifest long-term ( approximately 2 month) expression of liver-specific activities including cytochrome P450 enzyme activity and the synthesis of albumin, fibrinogen, transferrin, and other proteins. PC also undergo proliferation in association with stromal cells that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 64 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…One study showed a 12‐ to 15‐fold increase in mRNA levels for CYP2B1 after 7 days of induction of cocultures by phenobarbital as compared to hepatocytes cultured alone (81). Although each isoenzyme shows a different induction pattern, some have been reported to be inducible for up to 2 months (82). On the other hand, cocultivation does not preserve all isoenzyme activities; some, such as 2C11, 2C6, and 2E1, were reported to decline continuously (45, 46, 79, 80).…”
Section: Effect Of Coculture On Hepatocyte Morphology and Functionmentioning
confidence: 99%
“…One study showed a 12‐ to 15‐fold increase in mRNA levels for CYP2B1 after 7 days of induction of cocultures by phenobarbital as compared to hepatocytes cultured alone (81). Although each isoenzyme shows a different induction pattern, some have been reported to be inducible for up to 2 months (82). On the other hand, cocultivation does not preserve all isoenzyme activities; some, such as 2C11, 2C6, and 2E1, were reported to decline continuously (45, 46, 79, 80).…”
Section: Effect Of Coculture On Hepatocyte Morphology and Functionmentioning
confidence: 99%
“…Microstructure and conformational features of scaffolds have been demonstrated to govern level of differentiation and hepatocyte aggregate behavior in culture [7,8]. We have earlier demonstrated the suitability of textile scaffolds in inducing hepatocyte aggregate formation [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…with a synthetic matrix of biodegradable polymeric scaffolds composed of polyglycolic acid (PGA) (4,14). These cells produced albumin (4) and expressed cytochrome P450 enzyme activity that was measured by the ability of cells to transform the nonfluorescent compound ethoxy-fluoreseein ~To whom correspondence should be addressed: Boris Yoffe, M.D., VAMC (151B), 2002 Holcombe Boulevard, Houston, Texas 77030. ethyl ester to fluorescein (14). Hepatocyte cultures have also been maintained with an artificial capillary system and a hollow fiber binreactor with cells entrapped in collagen (9,21).…”
Section: Introductionmentioning
confidence: 99%